Central inspection teams and the enforcement of environmental regulations in China. Issue 112 (October 2020) - Xiang, C.; van Gevelt, T.
Highlights: We partially reconstruct the deployment of Central Environmental Inspection Teams (CEITs) in Hebei province. We find CEITs to be a relatively blunt yet effective institutional solution to enforcing environmental regulations in China. CEITs are highly resource intensive, may generate unintended governance outcomes and have distributive implications. Abstract: Despite the existence of a comprehensive set of environmental regulations, China's environmental issues continue largely unabated and are increasingly leading to discontent among its citizens. Mirroring recent governance trends in China, the central government has increasingly taken a more hands-on-role to ensure the enforcement of environmental regulations by local government officials. One manifestation of this effort to re-centralize environmental institutions has been the establishment and deployment of Central Environmental Inspection Teams (CEITs). CEITs report directly to the central government and are dispatched to carry out crackdowns where the central government has reason to believe that environmental regulations are not being enforced. With over 29, 000 companies fined and around 18, 000 local government officials disciplined, the CEIT has been heralded as a great success by the central government. Using a combination of primary and secondary data, we partially reconstruct the inaugural CEIT deployment in Hebei province in 2016 from the perspectives of government officials, private and state-owned companies, and local residents. While we generally find that the CEIT has proven effective in identifying and rectifying violations of environmental regulations, as an institutional solution it is inefficient and highly-resource intensive, likely to generate unintended governance outcomes in the medium-to-longer run, and has significant social justice implications.